Distribuição de crédito para agricultura familiar: um estudo do PRONAF a partir de um indicador de desenvolvimento rural - Silva, Fernanda Faria (2006)
The National Program for the Development of Familiar Agriculture (PRONAF) has brought an advance in terms of increasing the access and inclusion of familiar farmers regarding the formal agricultural credit, which was directed mainly for bigger farmers. During PRONAF early years, one observed that resources were concentrated both in the Brazilian regions of Southeastern and South and in familiar farmers already integrated to the agricultural market. Recently, some changes would modify theoretically the program profile, with resources being directed to a bigger number of lacking farmers. Besides, these changes encouraged the local development and incorporated the debate on the Territorial Development Paradigm . In this regard, this dissertation aims to verify the logic of the recent resource distribution of PRONAF main modalities, Credit and Infrastructure, by evaluating the profile of familiar farmers and agricultural localities that received them in the Northeast and South of Brazil. For that, we studied the inclusion criteria of familiar farmers and cities that collect these modality resources most. Next, based on the paper of Kageyama (2004), an Index of Rural Development was calculated to evaluate the economic development, social welfare and environment, population issues in these municipalities. Through statistical data analysis, we tried to verify if, even with the recent changes the legislation, PRONAF still follows the concentrative logic of resources defined according to the banking system requirements; that is, if the concentrative logic of other funding lines of the National System Agricultural Credit has prevailed.